Noise and structure of a gas jet at the choked outflow from a perforated disk - JUNGOWSKI, Wiktor M.; SELEROWICZ, Witold C. (Archives of Acoustics, 1976)
With the aid of experimental and theoretical investigations the main gasodynamic and acoustic properties of a gas jet discharging from a disk have been determined, and the range of efficient operation of the disk, as an element that reduces the outflow noise, has been established. The properties of the gas jet from a disk and a nozzle were compared.